Graduación. (UNED, 2024)
Aparecen en la mesa principal a la izquierda Nelson José Briceño Vargas - Administrador del Centro Universitario San José, Eugenia Chaves Hidalgo, Rodrigo Arias Camacho - Rector, Yinnia Mora Ordóñez, Beatriz Páez Vargas